Revolutionizing language learning beyond tradition in business education 4.0: Artificial intelligence-driven language learning towards english proficiency - Hasan Polas, Mohammad Rashed; Afshar Jahanshahi, Asghar; Samikon, Siti Aida; Akter, Tahmina; Roky, Md. Arif Hosseon (IGI Global, 2024)
This study investigates the interplay of attitude, learning environment, motivation, technological adaptability, and self-confidence with English language proficiency, leveraging artificial intelligence (AI) tools within the context of the Business Education 4.0 era among university students in Bangladesh. Methodologically, a quantitative approach was employed, embracing positivism. A stratified random sampling technique was applied, yielding a sample of 433 university students from five universities who are currently studying at the Department of Business Administration in Dhaka, Bangladesh. Structured surveys were used to collect data from the respondents. To analyze the data, SPSS V.25 was used. Findings reveal a significant positive association between a learning environment and English language proficiency. Technological adaptability, facilitated by AI, positively influences language skills. Self-confidence plays a crucial role, aligning with Bandura's Social Cognitive Theory. © IGI Global
Keywords: Educational innovations; Education—Data processing; Artificial intelligence—Educational applications